Technical efficiency of water use in the irrigated private schemes in Smar watershed, South-Eastern Tunisia - Mahdi N.; Sghaier M.; Bachta M.S. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
In this paper, Data Envelopment Analysis (DEA) is used to assess the farm-level technical efficiency measures and sub-vector efficiencies for water use of a sample of irrigated farms based on surface wells in Smar watershed (South-Eastern Tunisia). In the study area, private irrigation schemes play an important role in rural development, but the water scarcity and the increasing pressure on these resources call for a more efficient water use. With the Data Envelopment Analysis (DEA) techniques used to compute farm-level technical efficiency measures and sub-vector efficiencies for water use, it was shown that under Constant Returns to Scale (CRS) and Variable Returns to Scale (VRS) specification, substantial technical inefficiencies, of 26 percent and 15 percent respectively, exist among farmers. The sub-vector efficiencies for water proved to be even lower, indicating that if farmers became more efficient using the technology currently available, it would be possible to reallocate a fraction of the irrigation water to other water demands without threatening the goal of surface wells irrigation. In a second stage critical determinants of sub-vector efficiency are determined using a Tobit model. Farm size, age of the household head, the number of years of schooling, the type of irrigation scheme, crop choice and the irrigation methods applied showed a significant impact on the subvector efficiency for water. Such information is valuable for extension services and policy makers since it can help guide policies towards increased efficiency.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)